Time to 're-think' physical activity promotion for young people? Results from a repeated cross-sectional study. (December 2017) - Best, Paul; Tully, Mark; Corepal, Rekesh; Kee, Frank; Hunter, Ruth
Abstract Background The aim of this study was to investigate the relationship between knowledge of the current UK physical activity (PA) guidelines and amount of daily PA using a sample population of 11–16 year olds in Northern Ireland. Methods Cross-sectional survey data from the 2010 and 2013 Young Persons' Behaviour and Attitudes Survey of 10, 790 young people provided information on PA, knowledge of guidelines and socio-demographic characteristics. Multinomial logistic regression was used to investigate the associations between knowledge and amount of daily PA. Results Results from 2013 showed 67.0% of respondents were aware of PA guidelines with 15.4% reporting meeting them. Males were more likely to meet PA guidelines than females (OR 3.36, 95% CI 2.47, 4.59). Males who were active for 60 min or more, 7 days per week were less likely to be aware of guidelines (OR = 1.51, 95% CI 1.02, 2.24). For females, knowledge of PA guidelines had no significant association with amount of daily PA (OR = 1.74, 95% CI 0.99, 3.07). Those who did not enjoy being active were less likely to meet the guidelines (OR = 0.05, 95% CI 0.02, 0.12). Conclusions Knowledge did not appear to be an important predictor of PA in young people. Consequently, threshold based messaging containing recommended minimum PA guideline information may not be appropriate for this age group. Re-branding PA promotion to include the use of humour may offer a new direction for public health messaging based around fun and enjoyment.